The Factors Affecting Patient Safety Incidents (PSIs) Reporting at Indonesian Hospitals: A Literature Review - Dian Agnesa Sembiring; Miftahul Arsyi (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Underreporting of PSIs hampers efforts to improve service quality and patient safety (PS), as unreported incidents cannot be analyzed for future learning or prevention. This study employed a literature review method by searching online databases, including PubMed, Scopus, and Garuda Kemdikbud. The inclusion criteria were original articles published within the last five years, available in full text, open access, and written in English or Indonesian. A total of 33 articles met these criteria. The synthesis identified three main factors influencing PSI reporting in Indonesian hospitals: individual, organizational, and external factors. Individual factors include knowledge, attitudes and motivation, perceptions and fears, and demographic characteristics. Organizational factors consist of patient safety culture (PSC), leadership and management support, feedback mechanisms, reporting systems, and socialization and training. External factors are mainly related to government support and national policies.